Electrospun, synthetic bone void filler promotes human MSC function and BMP-2 mediated spinal fusion. (October 2020) - Glaeser, Juliane D; Salehi, Khosrowdad; Kanim, Linda EA; Ju, Derek G; Hyuk Yang, Jae; Behrens, Phillip H; Eberlein, Samuel A; Metzger, Melodie F; Arabi, Yasaman; Stefanovic, Tina; Sheyn, Dmitriy; W Bae, Hyun
Introduction: Synthetic bone grafts are often used to achieve a well-consolidated fusion mass in spinal fusion procedures. These bone grafts function as scaffolds, and ideally support cell function and facilitate protein binding. Objective: The aim was to characterize an electrospun, synthetic bone void filler (Reb) for its bone morphogenetic protein (BMP)-2 release properties and support of human mesenchymal stem cell (hMSC) function in vitro, and its efficacy in promoting BMP-2-/bone marrow aspirate-(BMA)-mediated posterolateral spinal fusion (PLF) in vivo. Methods: BMP-2 release kinetics from Reb versus standard absorbable collagen sponge (ACS) was determined. hMSC adhesion and proliferation on Reb was tested using cell counting, fluorescence microscopy and MTS. Cell osteogenic differentiation was quantified via cellular alkaline phosphatase (ALP) activity. For in vivo analysis, 18 Lewis rats were treated during PLF surgery with the following groups: (I) Reb + BMA, (II) Reb + BMA + BMP-2 and (III) BMA. A safe, minimally effective dose of BMP-2 was used. Fusion consolidation was followed for 3 months using radiography and micro-CT. After sacrifice, fusion rate and biomechanical stiffness was determined using manual palpation, biomechanical tests and histology. Results: In vitro, BMP-2 release kinetics were similar between Reb versus ACS. MSC proliferation and differentiation were increased in the presence of Reb. At 3 months post-surgery, fusion rates were 29% (group I), 100% (group II), and 0% (group III). Biomechanical stiffness was higher in group II versus I. Micro-CT showed an increased bone volume and connectivity density in group II. Trabecular thickness was increased in group I versus II. H&E staining showed newly formed bone in group II only. Conclusions: Reb possesses a high protein binding affinity and promotes hMSC function. Combination with BMA and minimal dose BMP-2 allowed for 100% bone fusion in vivo. This data suggests that a minimally effective dose of BMP-2 can be used when combined with Reb.